VALIDITY AND RELIABILITY OF THE FLOURISHING SCALE: LATVIAN VERSION - Sadauska, Inese; Koļesovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The objective of this study was to assess the psychometric properties of the Latvian version of the Flourishing Scale (FS), created by Diener et al. (2010). FS is a brief self-report measure of the respondent’s well-being and success in areas of relationships, self-esteem, purpose, and optimism. The scale provides a single score across 8 items. The original FS was translated to Latvian and then back to English. The Satisfaction with Life Scale and Meaning in Life Questionnaire was applied for testing the convergent validity of the FS. Participants of the study were 191 people, ranged in age from 19 to 68 (159 women, mean age M = 30.62, SD = 9.50). Reliability analysis, exploratory and confirmatory factor analysis (EFA and CFA) of the scale were performed. EFA indicated a one-factor structure. Results showed that the Latvian version of FS has good psychometric properties and demonstrated convergent validity. Testing of the original model by CFA resulted in acceptable fit indices.